Dependence of Blood Clot Lysis on the Mode of Transport of Urokinase into the Clot - A Magnetic Resonance Imaging Study in Vitro - Blinc, A; Planinšič, G; Keber, D; Jarh, O; Lahajnar, G; Zidansěk, A; Demsar, F (Thrombosis and Haemostasis, 1991)
Magnetic resonance imaging was employed to study the dependence of clot lysing patterns on two different modes of transport of urokinase into whole blood clots. In one group of clots (nonperfused clots, n1 = 10), access of urokinase to the fibrin network was possible by diffusion only, whereas in the other group (perfused clots, n2 = 10) bulk flow of plasma containing urokinase was instituted through occlusive clots by a pressure difference of 3 .7 kPa (37 cm H2O) across 3 cm long clots with a diameter of 4 mm. It was determined separately that this pressure difference resulted in a volume flow rate of 5.05 ± 2.4 × 10−2 ml/min through occlusive clots. Perfused clots diminished in size significantly in comparison to nonperfused ones already after 20 min (p <0.005). Linear regression analysis of two-dimensional clot sizes measured by MRI showed that the rate of lysis was more than 50-times faster in the perfused group in comparison to the nonperfused group. It was concluded that penetration of the thrombolytic agent into clots by perfusion is much more effective than by diffusion. Our results might have some implications for understanding the differences in lysis of arterial and venous thrombi.